Preserving Author Editing History Using Blockchain Technology - Pozi M.S.M.; Muruti G.; Bakar A.A.; Jatowt A.; Kawai Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Digital libraries; authorship contribution; Contribution rate; Scientific papers; Blockchain